RANCANG BANGUN SMART ROOM MENGGUNAKAN VOICE RECOGNITION BERBASIS ESP32 DAN BLYNK - jusdi; Adi Chandra; Nurwahid Syam (Institut Teknologi dan Bisnis Bina Adinata, 2023)
This study aims to: 1) To design a smart room using voice recognition based on esp32 and blynk. 2) To implement innovative room design using voice recognition based on esp32 and blynk.The research method used in this study is a research method adopted from Research and Development (R & D) with 6 stages, namely (1) potential, (2) information gathering, (3) design, (4) validation, (5) Revision, (6) trials, carried out directly at the research location.The results of this study are (1) The process of making this tool takes about 20 days because the components used are ordered online so you have to wait approximately 1 week. When making this tool, it is only constrained by time, both when assembled, then programmed after programmed tested, and then calibrated the temperature in the room after going through several stages of the tool.